Analysis Of Condom Use Behavior, Number Of Partners, And Injecting Drugs With The Incidence Of Hiv/Aids In Indonesia: A Systematic Review And Meta Analysis - Masnarivan, Yeffi; Khairiyah, Fatimah; Maharani, Diva; Yelna, Humaira Fajra; Zachrany, Nada Qarisa (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background: HIV/AIDS is a global health problem. HIV epidemic is a major problem and challenge for public health in the world, including Indonesia. HIV transmission can occur through the exchange of various body fluids from an infected person. The incidence of HIV/AIDS is also influenced by various risk factors. Methods: Systematic review and meta-analysis were carried out and were based on the PubMed, Sciencedirect, and Google Scholar databases with search ranges from 2012 to 2022. The articles analyzed were case-control study design articles and were prepared according to PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses). Results: Behavioral variables of using condoms in sexual intercourse, having more than one partner, and injecting drug use are at risk for the incidence of HIV/AIDS in Indonesia, which are indicated by a significance p-value less than 0.05. Conclusion: Variables that have a risk for HIV incidence in Indonesia are the behavior of using condoms, the number of partners, and injecting drug use. These three variables are evidenced by significant p-values. Keywords: HIV/AIDS, behavior, Indonesia, meta-analysis